Investigation of the Effect of SO2 and H2O on VPO-Cr-PEG/TiO2 for the Low-Temperature SCR de-NOx - Jia, Yong; Yang, Jianhua; Jiang, Jin; Gu, Mingyan; Zhi, Yingying; Guo, Lina; Chen, Yihua (Frontiers in Materials, 2019)
A catalyst 0.1VP(0.2)O-Cr(0.01)-PEG(1×10-4)/Ti for low-temperature SCR de-NOx was developed and the effects of SO2 and water vapor on its catalytic activity were investigated. Cr doping increases the molar ratio of V5+ to V4+ on the VPO catalyst, which promote oxidation of NO to NO2 and catalytic activity of the VPO catalyst. An appropriate amount of redox-coupled V5+/V4+ also promotes catalytic activity of the VPO catalyst. The denitration efficiency over 0.1VP(0.2)O-Cr(0.01)-PEG(1×10-4)/Ti was above 98% at 150-350℃. Cr doping also promotes the generation of Lewis acid around V5+ center and BrØnsted acid (P-OH) on the VPO catalysts. The strong surface acidity of 0.1VP(0.2)O-Cr(0.01)-PEG(1×10-4)/Ti could restrain the adsorption of and oxidation of SO2. Characterization (FT-IR, TG) results indicate that nearly no sulfate was deposited on the surface of 0.1VP(0.2)O-Cr(0.01)-PEG(1×10-4)/Ti after activity test. The competitive adsorption of water molecules and nitric oxide on the catalyst surface decreases the catalytic activity of the VPO catalyst. The addition of Cr and PEG could increase the surface area and the exposure of active site of VPO catalyst, which also increase the unoccupied active sites of VPO catalysts in the presence of water vapor. The catalyst 0.1VP(0.2)O-Cr(0.01)-PEG(1×10-4)/Ti for low-temperature SCR de-NOx shows high catalytic activity and exhibits high resistance to SO2 and water vapor.